LncRNA SNHG15 promotes hepatocellular carcinoma progression by sponging miR‐141‐3p. Issue 12 (16th July 2019) - Ye, Junfeng; Tan, Ludong; Fu, Yu; Xu, Hongji; Wen, Lijia; Deng, Yu; Liu, Kai
Abstract: Small nucleolar RNA host gene 15 (SNHG15) is a long noncoding RNA (lncRNA), which promotes progression of multiple cancers. Its specific function in hepatocellular carcinoma (HCC), however, is uncertain. The aims of our study were, therefore, to explore the role of SNHG15 in HCC. SNHG15 and miR‐141‐3p expression were assessed via quantitative real‐time PCR (qRT‐PCR) in 58 paired HCC samples and adjacent matched adjacent normal tissues. CCK‐8 assay, flow cytometric examination, and wound healing/invasion assays were used to respectively assess how SNHG15 influences cell proliferation, the cell cycle, and the migratory and invasive potential of HCC cells. MicroRNA (miRNAs) that targeted SNHG15 was screened by Starbase2.0 and identified by RNA immunoprecipitation and luciferase reporter assays. SNHG15 expression was markedly increased, whereas miR‐141‐3p expression was substantially reduced in HCC cells and tissue samples relative to normal controls. When SNHG15 was knocked down, this resulted in a significant disruption to the proliferation, as well as the invasive and migratory ability of these HCC cells. miR‐141‐3p was also found to be an SNHG15 target in HCC cells. Furthermore, miR‐141‐3p inhibitor partially reversed the observed SNHG15 depletion‐mediated reduction in HCC proliferation, migration, and invasion. By repressing miR‐141‐3p, SNHG15 could modulate zinc finger E‐box binding homeobox 2 (ZEB2) and E2F transcription factor 3 (E2F3) expression, both of which are miR‐141‐3p targets. These finding suggested that SNHG15 promoted HCC progression via negative regulation of miR‐141‐3p, thus identifying a potential novel HCC treatment pathway. Abstract : This paper showed that small nucleolar RNA host gene 15 (SNHG15) promoted hepatocellular carcinoma (HCC) progression by negatively regulating miR‐141‐3p, providing a new potential target for the treatment of HCC.